Factors that influence the reporting of child sexual abuse amongst primary school teachers in South Africa: an application of the theory of planned behaviour - Rule, Deirdre Margo (Department of Social Development, 2017)
Child sexual abuse is a prevalent problem in South Africa – one in every three children is sexually abused before the age of 18. Sexually abused children have serious psychological, physical and social problems which cause further difficulties into adulthood. Most abusers are known to their victims and thus, victims do not always disclose the abuse. Therefore, the law compels the reporting of child sexual abuse suspicions by third parties. However, past research shows that mandated reporters do not always report child sexual abuse suspicions. This study aimed to investigate the factors related to the mandatory reporting of child sexual abuse amongst primary school teachers in South Africa. A cross-sectional research study, using self-administered survey questionnaires, was conducted amongst foundation phase teachers in the Western Cape province of South Africa. Grounded on the theory of planned behaviour, this study investigated the relationships between various independent variables with the teacher's intention to report child sexual abuse. The independent variables tested included the teachers' attitude towards reporting, subjective norm, perceived behavioural control, knowledge on mandatory reporting, past reporting behaviour and socio-demographic characteristics of teachers. From a total population of 1118 public primary schools (and estimated 9542 foundation phase teachers), using stratified random sampling, a total of 2032 questionnaires were hand-delivered to 200 schools randomly selected across the Western Cape. A total of 399 foundation phase teachers participated in this study, representing a 20% response rate. This study found that about 25% of teachers had reported at least one case of child sexual abuse during their teaching career. About 7% of the teachers in this study had encountered instances in which they had failed to report suspected child sexual abuse. Subjective norm and perceived behavioural control (but not attitude towards reporting) was found to predict intention to report amongst teachers. A teacher who reported child sexual abuse in the past as well as a teacher with more accurate knowledge on mandatory reporting, was more likely to have intention to report in the future. Contrary to that posited by the theory of planned behaviour, attitude towards reporting did not mediate the relationship between past reporting behaviour and intention to report nor the relationship between knowledge on mandatory reporting and intention to report. The study further found that older teachers with more years teaching experience, although having a lower education level, were more likely to report their suspicions. Younger teachers, with less teaching experience, although better educated than their older counterparts, indicated less likelihood of reporting. The theory of planned behaviour, although significant, could not on its own effectively be applied to teachers' intention to report child sexual abuse and further investigation identified other explanatory factors that influenced teachers' intention to report. Given the high prevalence of child sexual abuse, the results have important implications. Whilst the teachers' age, years teaching experience or past reporting behaviour cannot be controlled, teachers must be adequately trained and supported. Knowing how to recognize and report child sexual abuse must be integrated into the tertiary education qualifications of student teachers as well as in continuing in-service training initiatives of current teachers. Furthermore, schools and the entire child protection system, must be supportive to teachers in their reporting duties.